2012
DOI: 10.1080/01446193.2012.688137
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of status and TMO workgroup cooperation: implications for project governance

Abstract: Achieving and sustaining the cooperation of individuals with their temporary multi--organisation (TMO) workgroups is, arguably, one of the most enduring challenges facing the construction sector. A mediational model connecting pride and self--respect to each of four dimensions of cooperative behaviour -in--role, compliance, extra--role, and deference -is tested in a survey sample of 140 construction professionals in Hong Kong. Bootstrap tests of the indirect effect of pride on cooperative behaviour suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 70 publications
2
2
0
Order By: Relevance
“…Of the 600 questionnaires sent out, 366 responses were received, with a response rate of 61%. This is comparable to previous SEM studies, such as that by Shan et al [76], with 188 cases, and by Anvuur and Kumaraswamy [77], with 153 cases (18% response rate). The responses exceeded the minimum of 100 cases necessary for SEM suggested by Gorsuch [78] and Bagozzi and Yi [79].…”
Section: Data Collectionsupporting
confidence: 91%
“…Of the 600 questionnaires sent out, 366 responses were received, with a response rate of 61%. This is comparable to previous SEM studies, such as that by Shan et al [76], with 188 cases, and by Anvuur and Kumaraswamy [77], with 153 cases (18% response rate). The responses exceeded the minimum of 100 cases necessary for SEM suggested by Gorsuch [78] and Bagozzi and Yi [79].…”
Section: Data Collectionsupporting
confidence: 91%
“…The results of this study show that trust has a significant moderating effect on both strong and weak opportunistic behaviors. The results are consistent with those of Anvuur et al [70,71]. These studies showed that in an environment where there is a high level of trust, contractors are willing to exchange information publicly and take the initiative to disclose the information to clients, such as pointing out loopholes in contracts.…”
Section: Moderating Role Of Trust Between Pro-client Risk Allocation ...supporting
confidence: 90%
“…The temporary nature of projects also has a negative impact on psycho-social aspects; for example, on the ability of team members to work together and to fully immerse themselves in the project (Bakker, Boroş, Kenis, & Oerlemans, 2013). This continuous absence of cooperation and boundary spanning behaviour in TMOs also has an impact on their performance (Anvuur, Kumaraswamy, & Fellows, 2012;Phua, 2004).…”
Section: Introductionmentioning
confidence: 99%